Faktor-faktor yang Mempengaruhi Pengambilan Keputusan dalam Melakukan Vaksinasi HPV pada Mahasiswa Kesehatan: Literature Review - Watari, Rekno; Handayani, Samsriyaningsih; Miftahussurur, Muhammad (Universitas Batanghari Jambi, 2024)
The research aims to analyze the factors that influence the administration of HPV vaccination to health students. The research method used is a literature review. The literature search uses data for the last 5 years from electronic databases such as PubMed, Science Direct, and Google Scholar. After fulfilling the inclusion and exclusion criteria, six articles were collected and discussed in the literature review. Literature results N=106, Pubmed N=53, ScienceDirect N=12, Google Scholar N=41. Six papers can be reviewed and fulfilled based on the inclusion criteria. Based on the results of the journal review, the research concludes that several things influenced health students in carrying out the HPV vaccination, knowledge about cervical cancer and HPV vaccination, attitudes and support for getting vaccinated, and exposure to social media